Current Status and Effectiveness of Artificial Intelligence Application in Police Law Enforcement in China - Sha, Jingying; Zhang, Wenhai; Qiu, Fengyuan; Jin, Gaofeng (Magyar Rendészet, 2025)
Currently, artificial intelligence, big data, cloud computing and other technologies are used in many aspects of policing in China. China’s 2024 Public Security Work Conference emphasised the need to accelerate the improvement of the “professional + mechanism + big data” new policing operation model and to comprehensively popularise the application of artificial intelligence in China’s police and law enforcement and enhance its effectiveness. This study utilises qualitative and quantitative research techniques to explore AI’s current status and effectiveness in Chinese police law enforcement. To improve the utilisation of AI in police law enforcement, this study also further explores the influencing factors and enhancement countermeasures of Chinese police officers’ willingness to use AI in police law enforcement. Study 1 used the survey method to select 180 civilian police officers in N city of F province to conduct a questionnaire survey, and 20 of them were randomly selected to conduct semi-structured interviews to clarify the current status of the application of AI in police enforcement in China. Study 2 randomly selected 200 public security police officers in the public security bureau of H city in Z province to conduct a contextual experiment, which used a between-subjects design of task type (objective/subjective task) + transparency (low/medium/high transparency) to analyse the factors affecting the willingness of Chinese police officers to use AI and to propose countermeasures. Study 1 found that the current Chinese police work, relying on artificial intelligence, has strengthened data collection and governance, promoted data sharing and application, and strengthened situational analysis and research and judgment, which has effectively improved the ability of social stability, control and management. However, there is a lack of scientific management mechanisms, and the police are unwilling to use them actively enough. The type of police work and the transparency of the algorithm can interact with the police’s trust in artificial intelligence and further affect their willingness to use it. Specifically, more complex subjective tasks can lead to the police’s willingness to use AI, but if the algorithm can be moderately transparent, the influence of task type will be reduced. Artificial intelligence has been used to a certain extent in China’s police reform to innovate police work mechanisms and improve the effectiveness of social governance. However, due to the lack of scientific management and training mechanisms, the police are not willing to use AI. Objective police work and moderate algorithmic transparency can enhance the police’s trust and willingness to use AI.